Cheap land Colorado : off-gridders at America's edge - Conover, Ted (Alfred A. Knopf, 2022)
"From Pulitzer Prize finalist and National Book Critics Circle Award-winning author Ted Conover, a fascinating portrait of a group of Americans living off-grid"--